Assessing the Performance of Bank Syariah Indonesia (BSI) through Shariah Conformity and Profitability (SCnP) Framework: A 2021-2023 Analysis - Riski Saputri; Khofifah Nur Hidayah; Maghfira Wilyaningtyas; Suci Nungcahyani (Presscience, 2024)
This study evaluates the performance of Bank Syariah Indonesia (BSI) using the Shariah Conformity and Profitability (SCnP) framework. The research focuses on the 2021-2023 period, utilizing a descriptive quantitative approach to analyze the bank's performance. The data employed in this study are secondary, derived from the annual financial reports of PT Bank Syariah Indonesia, obtained through its official website. The results reveal a significant shift in BSI's financial performance over the analyzed period. In 2021, BSI was positioned in the Upper Left Quadrant (ULQ), indicating moderate profitability with relatively lower alignment to Shariah principles. However, in 2022 and 2023, BSI transitioned to the Upper Right Quadrant (URQ), reflecting an improvement in both profitability and adherence to Shariah principles. These findings provide insights into the dynamic development of BSI's financial and Shariah performance, highlighting its progress toward achieving an optimal balance between profitability and Shariah compliance.